Селянська реформа на Катеринославщині (аналіз публікацій "Катеринославських губернських відомостей"). (Zaporizhzhia Historical Review, 2021)
This article is dedicated to the definition and analysis of the informative potential of the newspaper “The Ekaterinoslavskie gubernskie vedomosti’s” publications as historical sources for studying country reform in Ekaterinoslav province.